Medicinal Plants: A Prospect in Developing Male Fertility Enhancing Agent - Muhammad Ja’far Luthfi; Mahanem Mat Noor; Jalifah Latip (Biology, Medicine, & Natural Product Chemistry, 2015)
Medicinal plants have been a revolutionary breakthrough in the treatment of male sexual dysfunction. Traditional medicine based on a holistic philosophy is quite different with the practice of “western” medicine. Phytochemical substances focus their mechanisms of healing to the root of cause, i.e. the inability of controlling the proper function of the whole body system. Hence, medicinal plants manage sexual dysfunction and male fertility in the frame of sexual dysfunction as a whole entity. Some previous researches prove that the use of medicinal plants have a good impact in the treatment of a variety of male sexual problems. This paper will discuss several important aspects of aphrodisiac plants and preliminary study regarding them in Indonesia. Difficulties inherent to activity guided isolation and the specific requirements of bioassays are also discussed.